Do Patients with Luminal A Breast Cancer Profit from Adjuvant Systemic Therapy? A Retrospective Multicenter Study. - Joachim Diessner (PLoS ONE, 2016)
Luminal A breast cancers respond well to anti-hormonal therapy (HT), are associated with a generally favorable prognosis and constitute the majority of breast cancer subtypes. HT is the mainstay of treatment of these patients, accompanied by an acceptable profile of side effects, whereas the added benefit of chemotherapy (CHT), including anthracycline and taxane-based programs, is less clear-cut and has undergone a process of critical revision.In the framework of the BRENDA collective, we analyzed the benefits of CHT compared to HT in 4570 luminal A patients (pts) with primary diagnosis between 2001 and 2008. The results were adjusted by nodal status, age, tumor size and grading.There has been a progressive reduction in the use of CHT in luminal A patients during the last decade. Neither univariate nor multivariate analyses showed any statistically significant differences in relapse free survival (RFS) with the addition of CHT to adjuvant HT, independent of the nodal status, age, tumor size or grading. Even for patients with more than 3 affected lymph nodes, there was no significant difference (univariate: p = 0.865; HR 0.94; 95% CI: 0.46-1.93; multivariate: p = 0.812; HR 0.92; 95% CI: 0.45-1.88).The addition of CHT to HT provides minimal or no clinical benefit at all to patients with luminal A breast cancer, independent of the RFS-risk. Consequently, risk estimation cannot be the initial step in the decisional process. These findings-that are in line with several publications-should encourage the critical evaluation of applying adjuvant CHT to patients with luminal A breast cancer.